Repensando la relación entre los cambios sociales y los cambios legales en el buenos aires del siglo XIX - M. Shumway, Jeffrey (Revista de Historia Social y de las Mentalidades, 2011)
This  study  examines  connections  between  court  cases  of  family  conflicts  in nineteenth-century  Buenos  Aires  and  the  world  of  jurisprudence.  Although many  colonial  laws  continued  inplace  after  independence,  the  attitudes  of many judges’, lawyers’, and politicians’ toward those laws changed. The result was a shift in interpretation and application of the old laws, a shift that affected the daily lives of many porteños during the nation-building process.
Keywords: Law; Family; Independence